Protecting the Internet Without Wrecking It: The best solutions don't assume a zero-sum tradeoff between security and generativity.' - Zittrain, Jonathan (Boston Review)
In this article the author addresses what he sees at three fundamental critiques to his article that include the actual existence of an Internet security issue, the resolution of such issues by market forces, and the viability of his solutions. The author responds to each criticism in turn, stating that two Internet security problems exist, that market forces alone cannot be trusted to solve these issues, and his call for generative systems that are more social is, by its nature, initially vague and issues are worked out at a later date.